2014
DOI: 10.1074/jbc.m114.553370
|View full text |Cite
|
Sign up to set email alerts
|

Two p90 Ribosomal S6 Kinase Isoforms Are Involved in the Regulation of Mitotic and Meiotic Arrest in Artemia

Abstract: Background: Ribosomal S6 kinase (RSK) plays important roles in meiosis and mitosis. Results: Ar-Rsk1 promoted cdc2 phosphorylation and thereby meiotic arrest, whereas Ar-Rsk2 knockdown resulted in mitotic arrest. Conclusion: Ar-Rsk1, which lacks an ERK-docking motif, controls meiotic arrest, whereas Ar-Rsk2, which has an ERK-docking motif, controls mitotic arrest. Significance: The data provide insight into the functions of RSK isoforms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Artemia embryos are an excellent model for studying the regulation of cell quiescence, because they remain in this state for prolonged periods during diapause. Our previous studies attempted to elucidate the molecular mechanisms involved in the regulation of cell division during diapause embryo formation and termination by examining the roles of p90RSK, AMP-activated protein kinase, polo-like kinase 1, and H3K56ac (histone 3 acetylated on lysine 56) (41,(45)(46)(47)(48). These experiments indicated that the mechanisms underlying cell quiescence are complex and that epigenetic regulation plays an important role in the process of diapause formation and termination (48).…”
Section: Discussionmentioning
confidence: 99%
“…Artemia embryos are an excellent model for studying the regulation of cell quiescence, because they remain in this state for prolonged periods during diapause. Our previous studies attempted to elucidate the molecular mechanisms involved in the regulation of cell division during diapause embryo formation and termination by examining the roles of p90RSK, AMP-activated protein kinase, polo-like kinase 1, and H3K56ac (histone 3 acetylated on lysine 56) (41,(45)(46)(47)(48). These experiments indicated that the mechanisms underlying cell quiescence are complex and that epigenetic regulation plays an important role in the process of diapause formation and termination (48).…”
Section: Discussionmentioning
confidence: 99%
“…However, under the more acidic conditions in the matrix, one might hypothesize that the IF1 protein could depolymerize to active dimers and bind to the F1Fo ATP synthase, thereby preventing reversal of Complex V. of Plk1 during active mitosis was concluded to be inhibition of p90 ribosomal S6 kinase 1 (RSK1; i.e., Ar-RSK1) via blockage of its upstream activation pathway, MEK-ERK (mitogen/extracellular signal-regulated kinase; extracellular signal-regulated kinase). This linkage between Ar-RSK1 and the MEK-ERK signaling pathway required reevaluation when it was discovered that Ar-RSK1 does not possess a docking site for ERK (48). Rather, a second RSK protein was found in A. franciscana embryos (Ar-RSK2) that does possess the docking site.…”
Section: Crustaceansmentioning
confidence: 96%
“…In actively developing embryos, knockdown of Ar-RSK2 led to decreased levels of cyclin D3 and phosphorylated histone H3, and the production of pseudo-diapause cysts. Phosphorylation of Ar-RSK1 is now thought to block meiosis in A. franciscana oocytes (48). Most recently, expression patterns of microRNAs have been reported for A. parthenogenetica (205).…”
Section: Crustaceansmentioning
confidence: 98%
“…Upon liberation from females, cysts undergo profound reduction in metabolism and enter diapause, a state of developmental arrest and greatly enhanced stress tolerance (Clegg 1967(Clegg , 1997Clegg and Jackson 1998;King and MacRae 2012;Duan et al 2014). Diapause occurs in animals other than Artemia, most commonly in insects, and initiates in anticipation of adverse environmental conditions signaled by day length, perhaps via changes in circadian clock gene expression (Nambu et al 2004;MacRae 2010;King and MacRae 2015;Meuti et al 2015).…”
Section: Introductionmentioning
confidence: 99%